Fetal macrosomia: Definition, Prediction, Risk and Prevention. - Pacora Portella, Percy (2015)
Fetal macrosomia has been traditionally defined based on an arbitrary birthweight. However, fetal macrosomia is currently defined as a large for gestational age infant (>90 percentil) because of increased perinatal risk. This prospective investigation performed at San Bartolome's Hospital in Lima, Peru, included 1697 pregnant women from June 1990 to June 1993. 278 pregnant women had large infants (LGA) and 1 336 had normal sized infants. The predictor factors for LGA were: excessive weight gain (70%), male fetal sex (77%), placental width > 4 cm (74%), age over 30 years old (41,7%), obesity (33,5%), previous large infant (27%), fasting blood sugar > 79 mg/cIl (21,6%), 2h  post  prandial glucose > 110 mg/dl (20,7%), height > 160 cm (20%), familial diabetes (13,7%) and anemia (10, 1 %). The predictable maternal complications were: excessive weight gain, anemia, threatened abortion, placenta prove, polihydramnios, cord twist, arterial hypertensionassociated with premature rupture of membranes, dysfunctianal labor with prolonged second stage because of feto  pelvic disproportion and shoulder dystocia. We recomned to avoid and treat obesity before pregnancy, to discover risk factors at antenatal clinic and use caloric restriction, prophylactic insulin and induction of labor before 42 week of gestation in order to avoid fetal macrosomia.